Quantum machine learning - Rot, Miha (Matrika, 2019)
Advances in processing power and algorithms have made machine learning a very potent tool. This article attempts to introduce machine learning and present two applications of machine learning in quantum physics. The first example deals with the ground state energy of an electron in 2D potential, while the second one touches upon the applicability of machine learning to the quantum many-body problems. The article concludes with a brief description of potential machine learning speed-ups promised by quantum computers.
Keywords: kvantna mehanika; machine learning; quantum mechanics; strojno učenje